Beyond mere assumptions, are public workers resistant to change? - Oliveira, Jefferson Menezes de; Estivalete, Vania de Fátima Barros; Moura, Gilnei Luiz de; Campos, Simone Alves Pacheco de (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
In order to question the belief that public servants are predominantly resistant to change, this study intended to measure the level of resistance to change among public servants of a federal education institution located in Brazil’s south. To overcome presumptions, we sought to elucidate the prominent types of attitudes towards change by means of a survey applied to 207 staff members of the institution. The results of the evaluation made it possible to demystify a traditionalist view of public organizations, according to which public servants are considered resistant to change. In the institution studied, there was openness and acceptance to change as a central principle. In addition, the study has contributed to cushion beliefs both that older staff members resist more and that technicians do more than teachers.